Chickens, more than humans, focus the diversity of their immunoglobulin genes on the complementarity-determining region but utilise amino acids, indicative of a more cross-reactive antibody repertoire - Mallaby, Jessica; Ng, Joseph; Stewart, Alex; Sinclair, Emma; Dunn-Walters, Deborah; Hershberg, Uri (Frontiers in Immunology, 2022)
Mechanisms of B cell diversification differ greatly between aves and mammals, but both produce B cells and antibodies capable of supporting effective immune response. To see how differences in diversity might affect overall repertoire diversity we have compared the diversity characteristics of immunoglobulin genes in the domestic chicken to one of the most documented and studied mammalian species – humans. Both use VDJ recombination and somatic hypermutation, but only the chicken uses somatic gene conversion. A range of diversity analysis tools were used to investigate multiple aspects of amino acid diversity at both the germline and repertoire level. Assessment of the effect of differing amino acid usage on antibody characteristics was undertaken. At both the germline and repertoire level chickens exhibited lower amino acid diversity in comparison to the human immunoglobulin genes, especially outside of the complementarity determining region (CDR). Chickens were also found to possess much larger and more hydrophilic CDR 3s that have a higher protein binding potential suggesting that the antigen binding site in chicken antibodies are more flexible and more broadly reactive than that seen in human antibodies.